The Association between Positive Antenatal Depression Screening and Breastfeeding Initiation and Continuation - Stark, Elisabeth L.; Shim, Jessica; Ross, Carolyn M.; Miller, Emily S. (American Journal of Perinatology, 2019)
Objective This study was aimed to determine the association between antenatal depression and breastfeeding initiation and continuation at 6 weeks postpartum.Study Design This retrospective cohort study included all live-born deliveries after 24weeks' gestation at a single tertiary care institution between 2009 and 2014 with a documented antenatal depression screen using the Patient Health Questionnaire-9 (PHQ-9). During the study period, it was recommended that routine screening occur during both the first and third trimesters. A positive screen was defined as a PHQ-9 score ≥ 10. Breastfeeding initiation and continuation until 6 weeks' postpartum were compared between women with and without a positive screen using bivariable analyses. Stepwise backward elimination regressions were used to identify whether a positive screen was independently associated with breastfeeding rates after controlling for confounders.Results Among the 2,871 women meeting inclusion criteria, 302 (10.5%) were screened positive for antenatal depression. After adjusting for confounders, there were no differences in breastfeeding initiation (adjusted odds ratio [aOR] = 0.78, 95% confidence interval [CI]: 0.52–1.16), but women with a positive antenatal depression screen were significantly less likely to continue breastfeeding at 6 weeks' postpartum (aOR= 0.67, 95% CI: 0.48–0.96).Conclusion A positive antenatal depression, screened in the first or third trimester, is a significant risk factor for early breastfeeding cessation.
Keywords: breastfeeding; antenatal depression; postpartum depression; disparity